Awareness of Oral Hygiene among Dental Students-A Survey - Pravalika1 , Keerthi Sasanka2 , Gifrina Jayaraj3 , Dhanraj Ganapathy4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Attitudes of dental students toward their own oral health affect their oral health habits and also have apossible influence on the improvement of the oral health of their patients and society.The aim of this surveyis to create awareness among dental students on oral hygiene.A survey with 17 questions was prepared andsent via google forms to 100 dental students.The responses were collected and analysed.Most of the dentistsare aware that oral health determines the overall health of an individual.Many among the population usemouthwash,rinsing with water etc to avoid bad odour. Aspects of a dental student’s oral health attitude andbehavior improved but this improvement was limited.Thus, the students should be motivated to become anexample of oral health for the society, for which few steps to motivate them toward better oral health areproposed.This approach would also be helpful in disseminating positive oral health concepts to the generalpublic.